Internal service quality and external service quality using two versions of SERVQUAL scale: An empirical evidence from five malls in the capital city of Saudi Arabia - Bader M. Almohaimmeed (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Much of service quality research has been carried out on external service quality, i.e., services delivered by organizations to their own customers. The aim of this study was to investigate the influence of internal service quality (ISQ) on external service quality (ESQ), under the existence of variables such as learning organization (LO), employee job satisfaction (ES) and employee loyalty (EL). The study posited three conceptual models from which the best one was adopted based on the results of goodness of fitness indices. The sample comprised 500 employees working in five malls in the capital city of Saudi Arabia and 500 customers visited the same places during data collection process. The required data was collected using a questionnaire administered to the participated employees and customers. Out of the distributed questionnaires, 367 questionnaires were returned from employees and 384 questionnaires from customers. Returned questionnaires were analyzed using IMBSPSS.23 and AMOS.22. The results revealed a non-significant influence of LO on ISQ. From employees' viewpoints, ISQ was regarded as a main driver of their satisfaction and but not of their loyalty. Nevertheless, the findings showed that both employee job satisfaction (EM_SAT) and employee loyalty (EM_LOY) have significant influences on ESQ as measured on the basis of customers' perspectives. Lastly, ISQ has a significant impact on ESQ.
Keywords: L81; M3; M19; M31; 650; external service quality; internal service quality; employee loyalty; employee job satisfaction; employee-based SERVQUAL; customer-based SERVQUAL